Jihad dalam Konteks Ḥadīš Aḥkām dan Kontekstualisasi Maknanya di Era Milenial - Muhammad Gazali Rahman; Aisma Maulasa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2021)
Prophet Muhammad left two very valuable legacies, namely the Qur'an and Hadith. These two legacies have always been the main source of reference for anyone in solving the myriad of life's problems. The complexity of human life in the end also demands the reading and review of applicable sources that have been appreciated by the Prophet Muhammad on his period to be contextualized and exist all the time. Likewise, the emergence of modern challenges that tend to reduce the authority of prophethood is a challenge for Muslims to reconstruct the religious foundations that have long been the formal law in interacting. This research is library research which is analyzed with a normative approach and a contextual approach. The results of this study indicate that as part of Islamic teachings, jihad in the early Islamic narrative may be different from the current version of jihad, either due to contextualization of meaning or due to a reduction in the true essence of jihad.